SURVEY OF FALSE SMUT (USTILAGINOIDEA VIRENS) OF RICE (ORYZA SATIVA L.) IN SELECTED DISTRICTS OF UTTAR PRADESH, INDIA - SHIVAM SINGH; ABHILASHA A. LAL; SOBITA SIMON (The Bioscan, 2014)
A survey was carried out in selected districts of Uttar Pradesh (India) to evaluate the incidence of false smut of rice. Among all districts surveyed, the highest incidence (80%) was recorded in Gaur block of Basti district. The incidence ranged between 5-80% in surveyed districts of Uttar Pradesh (India). After the survey, the data imply that false smut is emerging as one of the major diseases of rice in India.